Final whistle or beyond? Temporal dynamics of anxiety and psychological recovery in women’s soccer - Sulu, Buse; Kayğusuz, Şeval; Çakaloğlu, Erdem (Frontiers in Psychology, 2025)
Anxiety and emotions have been identified as fundamental determinants of psychological recovery. While positive emotions and self-confidence facilitate athletes’ ability to regain balance and recover psychologically in the face of challenges, negative emotions together with cognitive and somatic anxiety may hinder this process. In this regard, it is important to examine psychological recovery in conjunction with anxiety and emotions to capture its dynamic nature. The aim of this study was to investigate the role of emotions and anxiety in athletes’ psychological recovery and to evaluate their seasonal changes. The sample consisted of 20 female soccer players from Kastamonu Gücü Sports Club, competing in the Women’s 2nd League Group C in the 2023–2024 season. Analyses were conducted using R (version 4.4.1; R Core Team, 2024) with linear mixed-effects models (LMM). The models included both fixed effects and random intercepts for athletes. Analyses were performed with the lme4 and lmerTest packages, while model fit indices and explained variance were calculated using the MuMIn and performance packages; model assumptions were tested and VIF values were reported. The findings revealed that psychological recovery was supported by self-confidence and positive emotions, whereas cognitive/somatic anxiety, anticipated match difficulty, and negative emotions weakened it. In addition, a decline in recovery was observed as the season progressed. The models explained a large proportion of the variance in psychological recovery (R2m ≈ 0.60–0.65). The contribution of individual differences was limited (ICC ≈ 0.11–0.14), suggesting that shared seasonal processes were more influential than individual-level factors. In conclusion, psychological recovery is a dynamic process shaped by both protective (self-confidence, positive emotions) and risk-related (anxiety, anticipated match difficulty, negative emotions) factors. The seasonal decline underscores the importance of systematically integrating practices to support psychological recovery to sustain performance throughout the season.